Adapting PRISMA for software development in rural areas: A mobile-based healthcare application case study - Siew, Siang Ting; Yeo, Alvin Wee (IEEE, 2012)
This paper reports on the use of a proposed methodological framework called PRISMA (Participatory Action Research in Software Development Methodology Augmentation) to support and design a mobile-based healthcare application for a remote Penan community in Malaysian Borneo. PRISMA employs participatory action research (PAR). The approach has been successfully applied in projects with rural communities. The intent of PRISMA is to strengthen community participation and local management in order to ensure software system is built at interest of community. The healthcare application is targeted at young school-children and mothers as they have a major influence on health issues affecting their family. A key aspect of PRISMA is the active participation of multiple stakeholders - in our case, the villagers, medical doctors, researchers as well as teachers, who will be assisting in the monitoring of the usage and health change process for the children. Preliminary results of the health intervention will be reported.